2018
DOI: 10.30845/ijll.v5n4p9
|View full text |Cite
|
Sign up to set email alerts
|

TED Talks: An Approach for Activating the World Knowledge Schema of EFL Writers

Abstract: The lack of reading culture among our youth today, especially in the Arab world, has greatly limited their ideas and affected the quality of their writing. Due to their underdeveloped world-knowledge schema, they lack creativity, struggle with the brainstorming step or even skip it, and, consequently, produce essays that lack sufficient content and maturity of ideas. Hence, not only is activation of prior knowledge required but also the amount of activation is to be considered. Accordingly, the purpose of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
2
1
0
1
Order By: Relevance
“…When examining the effects by country, the meta-analysis revealed that TED Talks were most effective in improving speaking skills for university students in Egypt and Saudi Arabia, both showing substantial positive effects categorized as "very high." This finding aligns with previous studies highlighting the benefits of using authentic multimedia resources like TED Talks for language learning in Arab contexts (Aljohani, 2019;Harb, 2018;Shawqy et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…When examining the effects by country, the meta-analysis revealed that TED Talks were most effective in improving speaking skills for university students in Egypt and Saudi Arabia, both showing substantial positive effects categorized as "very high." This finding aligns with previous studies highlighting the benefits of using authentic multimedia resources like TED Talks for language learning in Arab contexts (Aljohani, 2019;Harb, 2018;Shawqy et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…The data obtained are broadly consistent with the major trends in modern pedagogy so far, developed by Rubenstein (2012), Takaesu (2013), Harb (2018), Rudneva et al (2019), Wu (2020), and others. That is a completely positive effect of TED Talks integration into the classroom for increasing students' language competence precisely listening comprehension.…”
Section: Discussionsupporting
confidence: 89%
“…A lot of attention was dedicated to methodology and different learning techniques. Harb (2018) studied the integration of Information and Communication Technologies in mastering writing proficiency on the example of Lebanese students. The scientist investigated the utility of TED Talks videos as a motivation tool that activated prior knowledge rather quickly (p.76).…”
Section: Introductionmentioning
confidence: 99%
“…Acredita-se que este é um dos métodos mais eficientes para melhorar as habilidades de discurso monólogo (DM), já que esses materiais não são apenas gravações de áudio de material educacional, mas exemplos de inglês ao vivo com seu ritmo, vocabulário, tom, sotaques, gestos e expressões faciais dos falantes. Os vídeos TED Talks oferecem muitas oportunidades para aprender a falar em público e desenvolver o pensamento crítico, além de serem altamente informativos, permitindo que os alunos aprendam muitas informações novas e interessantes em sua área profissional (KOSTROMINA et al, 2022).…”
Section: Introductionunclassified